Growing Geo-economic and Geo-strategic Interests of India in Afghanistan: Implications for Pakistan - Umbreen Javaid; Tehmina Aslam (Journal of Political Studies, 2016)
The tragic event of 9/11 changed not only the global political environment of the world but also altered the security and political environment of South Asian region. A change in Pakistan’s foreign policy towards Afghanistan was witnessed. Since Pakistan’s emergence as a separate independent state, its dispute with Afghanistan on Durand Line has substantially influenced the course of its foreign policy towards Afghanistan. The issues in Afghanistan directly affect Pakistan in the domain of politics, economics and society. The troubled relations between the two states gave a chance to India to win the sympathies of Afghanis after 9/11.India emerged as a strong regional player and established good relations with Afghanistan by helping them. To secure its interests in Afghanistan India also established good relations with Iran. They share some common motives. Both the countries abominate the Taliban regime in Afghanistan and feared of the exportation of militants to their own soil. So far friendly ties between India and Afghanistan always remain as a source of anxiety for Pakistan. India participated in Bonn Conference 2001 which underlined the base of political and constitutional structure for Afghanistan. India is regarded as a positive actor by most of Afghans contrary to Pakistan. The paper examines the strategic interests of India in Afghanistan and its subsequent impacts on Pakistan.